A NON-ZERO SAMPLING PLAN FOR THE MODERATION OF EXAMINATION PAPERS - Van Wijk, S.A. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: The moderation of examination answer books is an area where quality assurance is essential, and should be employed to ensure that an examination paper